Caleb Williams - Godwin, William, 1756-1836 (Oxford world's classics (Oxford University Press), 2009)
'He appears to be persecutor and I the persecuted: is not this difference the mere creature of the imagination?' Caleb is a guileless young servant who enters the employment of Ferdinando Falkland, a cosmopolitan and benevolent country gentleman. Falkland is subject to fits of unexplained melancholy, and Caleb becomes convinced that he harbours a dark secret. His discovery of the truth leads to false accusations against him, and a vengeful pursuit as suspenseful as any thriller. The novel is also a powerful political allegory, inspired by the events of the decade following the French Revolution. This new edition reproduces the original novel of 1794, which captures the raw indignation and sense of injustice felt by victims of British law. It includes the startlingly different manuscript ending, and selected variants in the second and third editions reflecting changes in Godwin's political and philosophical thinking.